Apakah Religiusitas Dan Ideologi Etis Benar-Benar Penting? Sebuah Perspektif Dari Hubungan Antara Love Of Money Dan Perilaku Tidak Etis Para Akuntan - Tri Hanani; Paradisa Sukma; Novia Rizki; Wulandari Agustiningsih; Victoria Kusumaningtyas Priyambodo (Fakultas Ekonomi dan Bisnis Unram, 2026)
Financial statements are a crucial element of an accountant's preparation. However, accountants often engage in unethical behavior toward financial statements, one of which is based on a love of money. This study aims to determine the moderating impact of ethical ideology and religiosity on the relationship between love of money and unethical behavior. This is a quantitative study using a questionnaire as the data collection technique. Data processing with a total of 205 respondents revealed a significant impact of love of money on the tendency for unethical behavior in accountants. This implies that one of the root causes of unethical behavior in accountants is an excessive love of money. This study also provides empirical evidence that intrinsic religiosity can weaken the impact of love of money on unethical behavior, while extrinsic religiosity does not. This implies that the deeper and more internalized a person's religiosity, the lower the impact of love of money on the tendency for unethical behavior.